2001
DOI: 10.1191/026921601678320269
|View full text |Cite
|
Sign up to set email alerts
|

The concerns of patients under palliative care and a heart failure clinic are not being met

Abstract: Patients with a terminal illness, identified by palliative care teams working in Manchester, and patients attending a heart failure clinic, were asked to participate in a prospective survey to determine their main concerns. Data were collected from 213 palliative care (PC) patients (mostly with cancer) and 66 patients with heart failure (HF). The median ages of the two patient groups were similar, but the HF patients were more likely to be male and living with a partner; 13% of PC and 7% of HF patients reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 8 publications
5
58
0
3
Order By: Relevance
“…Bredart et al (2001) found that patients valued the provision of medical information and wanted this to be improved. Anderson et al (2001) estimated that between 24% and 31% of social functioning problems reported by patients have not been addressed by professionals.…”
Section: Article In Pressmentioning
confidence: 99%
“…Bredart et al (2001) found that patients valued the provision of medical information and wanted this to be improved. Anderson et al (2001) estimated that between 24% and 31% of social functioning problems reported by patients have not been addressed by professionals.…”
Section: Article In Pressmentioning
confidence: 99%
“…Most (19) of the studies employed quantitative surveys (using highly structured methods in questionnaire or interview modalities); 4 were qualitative studies (using semi-structured interviewing), in individual or focus group formats). In studies using quantitative designs, the most commonly applied assessment of unmet needs was the Supportive Care Needs Survey (SCNS; used in six studies) -although there were inconsistencies between studies in how this measure was used (adaptations to questionnaire length, items, dimensionality, and language).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Therapy aimed at reduction of HF symptoms may also prolong life, or at least be perceived to do so. This may create confusion in the minds of both the patient and health care provider as to the actual goals of therapy -that the goal may be primarily to prolong life rather than primarily to alleviate symptoms (19). This may lead to the unintended expectation that other therapeutic modalities, such as mechanical device therapy or cardiopulmonary resuscitation, may also be required, when in fact they may not be appropriate (20).…”
Section: What Have We Learned Andmentioning
confidence: 97%